NLRP3 Inflammasome May Be a Biomarker for Risk Stratification in Patients with Acute Coronary Syndrome - Mo DG; Wang L; Han QF; Yu K; Liu JH; Yao HC (Dove Medical Press, 2022)
De-Gang Mo,1 Lin Wang,2 Qian-Feng Han,1 Kang Yu,3 Jia-Hui Liu,1 Heng-Chen Yao1 1Department of Cardiology, Liaocheng People's Hospital Affiliated to Shandong First Medical University, Liaocheng, People's Republic of China; 2Cardiologic Color Doppler Room, Liaocheng People's Hospital Affiliated to Shandong First Medical University, Liaocheng, People's Republic of China; 3Department of Laboratory Medicine, Liaocheng People's Hospital Affiliated to Shandong First Medical University, Liaocheng, People's Republic of ChinaCorrespondence : Heng-Chen YaoDepartment of Cardiology, Liaocheng People's Hospital Affiliated to Shandong First Medical University, Liaocheng, 252000, People's Republic of China, Email yaohc66@126.comPurpose: Acute coronary syndrome (ACS) has a high incidence and mortality rate worldwide, which has a considerable negative impact on the global economy. This study aimed to identify a group of ACS patients at a high risk of recurrent adverse cardiac events using the plasma NLRP3 inflammasome.Patients and methods: ACS patients admitted to Liaocheng People's Hospital between June 2021 and March 2022 were enrolled in this study. Patients were divided into low (levels < 3.84 ng/mL) and high (levels ≥ 3.84 ng/mL) groups based on the median NLRP3 inflammasome levels. The patients were divided into three groups according to the Thrombolysis in Myocardial Infarction Risk Score for Secondary Prevention (TRS-2P): low (scores ≤ 2 points), intermediate (scores = 3 points), and high (score ≥ 4 points) risk. We investigated the relationship between NLRP3 inflammasome and laboratory indicators. Additionally, we examined whether the NLRP3 inflammasome was an independent predictor of high TRS-2P and explored the applicability of the plasma NLRP3 inflammasome for predicting high TRS-2P.Results: Logistic regression analysis revealed that NLRP3 inflammasome was an independent predictor of high TRS-2P (odds ratio [OR]:2.013; 95% confidence interval [CI]: 1.174- 3.452). The area under the receiver operating characteristic curve value of the NLRP3 inflammasome was 0.674 (95% CI: 0.611- 0.737; P < 0.001).Conclusion: NLRP3 inflammasome levels are an independent predictive factor for high TRS-2P levels, which indicates that the NLRP3 inflammasome may help predict the prognosis of ACS patients.Keywords: NLRP3 inflammasome, biomarker, risk stratification, acute coronary syndrome, thrombolysis in myocardial infarction risk score for secondary prevention, TRS-2P